O fazer docente na educação básica : abordando o conceito de pensamento computacional de forma transversal - Wasserman, Camila (2021)
This research sought to investigate the teachers' perceptions about their performance and preparation to work with Computational Thinking (CT) concepts as indicated in the BNCC (Brazilian National Curricular Base). The new curricular organization's change based on competencies, skills, and attitudes to be built in the students, demanding a different conception from the one we were used to working and how we do the teachers education. When BNCC mentions the tripod (digital world, digital culture, and digital education), the elements that make up this "new" contemporary thinking point out to active methodologies, entrepreneurship, innovation, creativity, computational thinking, and others, if we adopt the traditional model of dealing with these elements, we will make disciplines with content associated with these themes. However, more critical than the significant increase in workload, is the issue of maintaining the knowledge sharing. In educational jargon, we call "boxes" that represent the subjects in the curriculum. In this scenario, CT was chosen as the theme of this investigation, being understood as a tool to build a solution strategy applied in any knowledge area. The research used a qualitative approach of an exploratory nature, supported by a case study with teachers who work in the public K-8 system, from schools of the Brazilian south city Viamão. The research findings show that the teachers have desire to learn, understand, and apply the concept of computational thinking in their daily activities. However, for the concept to come alive in the classroom, investments are needed in teacher education. As an additional contribution, a website with materials, tips, and resources to help those interested in the topic.